An algebraic approach to modelling and performance optimisation of a traffic route system - Obuchowicz, Andrzej; D'Souza, Kelwyn A.; Banaszak, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
An algebraic approach to performance optimisation of collision-free traffic route systems is presented. The proposed models take into account traffic conditions in a wide area and react to the dynamic nature of the traffic flow. The adjustment of traffic-signal timings to minimise the total travel time through a city is considered.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka